(untitled) (Biological Sciences - PJSIR, 2007)
Quanti tative anal ysis of essenti al oi l s of ma,joram , wh ich is grown in Jord an , yielded th ymol as m ajor compou nd . The y i eld of essential oi ls i ncreased w ith th e red uction of plant densi t y. Th e i ncrease i n n itrogen dose (from 50 to I 00 kg/h a) correlated w i th t h e i ncrease i n the y i eld of essentia l oi l s i n a ll h arvests, wh i l e wi th the i ncrease i n the dose of n i trogen from I 00- 1 50 kg/ha, the y i el d of essential oi l s decreased. On the other h and, th e n i trogen dose of 1 50 kg/ha correl ated with essential oi ls containi n g the h i gh est percentage of th ymol (53. 1 1 %). A strong relatio n was found between the y i eld and the chemi cal compositi on of marjoram essenti a l oi ls and applied agronomic treatments wh i ch requi re specia l atten t i on.